Penguatan bagi Guru dalam Meningkatkan Mutu Lulusan melalui Pola Kemitraan SMK dengan Dunia Usaha dan Dunia Industri - Yusuf, Muhammad; Abubakar, Abubakar; Siraj, Siraj; Taufiq, Taufiq (LPPM Umuslim, 2024)
This community service program is of high urgency, considering the challenges and demands within vocational education in Indonesia. With the advancement of technology and the emergence of Industry 4.0, the skills required by the industry are continuously evolving. Vocational schools need to adapt to these developments to ensure their graduates remain relevant in the job market. The implementation mechanism of this community service program follows stages of problem and needs analysis, offering partnerships with industry partners, carrying out activities, and evaluating the activities. The results obtained show that teachers have gained teaching skills that are more aligned with industry developments, enabling them to deliver content that meets the needs of the business world.